2005
DOI: 10.1016/j.puhe.2004.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of annoyance attributed to electrical equipment and smells in a Swedish population, and relationship with subjective health and daily functioning

Abstract: Annoyance related to electrical and/or chemical factors was common in a Swedish population. Subjects reporting environmental annoyance rated their overall health significantly poorer than the general population. The association with subjective health and functional capacity increased with severity of annoyance, which suggests that there is some connection between environmental annoyance, well-being and functional capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 32 publications
8
54
0
1
Order By: Relevance
“…On the other hand, it is possible that small differences in biological systems that do not attract the clinicians' immediate attention could, if given enough time, have a biologically significant effect. The fact that the EA group showed tendencies similar to those of the GA group in both self-reports and cortisol agrees fairly well with our results from previous experimental and epidemiologic studies on these groups (1,22). It appears that a congruent pattern of differences is traceable across different contexts, the EA group appearing more similar to the GA group in ratings of distress and health complaints than to the SA group (1).…”
Section: Generally Annoyedsupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, it is possible that small differences in biological systems that do not attract the clinicians' immediate attention could, if given enough time, have a biologically significant effect. The fact that the EA group showed tendencies similar to those of the GA group in both self-reports and cortisol agrees fairly well with our results from previous experimental and epidemiologic studies on these groups (1,22). It appears that a congruent pattern of differences is traceable across different contexts, the EA group appearing more similar to the GA group in ratings of distress and health complaints than to the SA group (1).…”
Section: Generally Annoyedsupporting
confidence: 89%
“…Annoyance related to electrical and chemical factors has been shown to be fairly common in the general population (1). In some cases, such nonallergic annoyance may develop into states of severe intolerance, such as idiopathic environmental intolerance.…”
mentioning
confidence: 99%
“…In the New South Wales adult health survey 2002 24.6% of the respondents reported sensitivity to chemical odours (Centre For Epidemiology And Research 2003). In Scania, Sweden 20.8% of the respondents to a questionnaire reported some or much annoyance to breathing air that smells of chemicals or other smells (Carlsson et al 2005), and in another Swedish study in Skövde 33% of the participants in a clinical examination reported general odour intolerance (Johansson et al 2005). Finally, in Germany 9% of the participants in a face-to-face interview survey reported that their body reacted immediately when exposed to chemicals (Hausteiner et al 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Sources of EMF that are reported to trigger symptoms vary and may include mobile phones, computer equipment, overhead powerlines, and domestic appliances [Röösli et al, 2004]. As well as being associated with unpleasant physical symptoms, IEI-EMF can lead to high levels of distress for sufferers and impair their ability to work and maintain normal social and family contacts [Röösli et al, 2004;Carlsson et al, 2005;Osterberg et al, 2007;Rubin et al, 2008]. The World Health Organization's (WHO) factsheet about IEI-EMF notes that ''EHS is characterized by a variety of nonspecific symptoms that differ from individual to individual.…”
Section: Introductionmentioning
confidence: 99%